27x+49=-167

Simple and best practice solution for 27x+49=-167 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27x+49=-167 equation:


Simplifying
27x + 49 = -167

Reorder the terms:
49 + 27x = -167

Solving
49 + 27x = -167

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-49' to each side of the equation.
49 + -49 + 27x = -167 + -49

Combine like terms: 49 + -49 = 0
0 + 27x = -167 + -49
27x = -167 + -49

Combine like terms: -167 + -49 = -216
27x = -216

Divide each side by '27'.
x = -8

Simplifying
x = -8

See similar equations:

| 1/-2+y=2/3 | | M^2+2m+1/m^2-2m-3=7 | | 10/-6 | | M^2+2m+1/m^2-2m-3=0 | | 56=42+u/11 | | 12+d/9=27 | | 4y-192=96 | | 9/-3-2x=9 | | -9-5x=-31 | | 6x-5x=45 | | (x+1)/5 | | -77-5x=-31 | | x^2+x+0.2925636=0 | | 13.04+x=28.96 | | 6(2x-5)-11x=8 | | 29-3x=2x+4 | | 13.04+x^5=28.96 | | 29x-13=306 | | 10y-2=7+3G | | 3b^2-b-7=4b(2b+3)-1 | | x/4=9/(2*x) | | 12n+3=-12n^2 | | 9x-14=40 | | 6h=4h^3+5h^2 | | 3m(2m+5)-8=2m(3m+5)+2 | | 3.5(x+2.2y)+2(2.2x+1.7y)= | | (-9y-2z)(-8)= | | 1/16w^2+1/8w=1/2 | | 3d-4=d(d+8) | | 44x-4x=5x+18 | | -7-5x=5x+21 | | 10a+8b+4c-8d=7 |

Equations solver categories